AN ANALYSIS OF THE DETERMINANTS OF FOREIGN DIRECT INVESTMENT IN TURKEY: THE ROLE OF THE INSTITUTIONAL CONTEXT - DUMLUDAĞ, DEVRİM (VILNIUS GEDIMINAS TECH UNIV, 2009)
This paper tries to empirically verify the argument that institutional factors such as enforcement mechanisms, political and economic stability, stable and reliable, transparent legal and regulatory framework and corruption are critical in explaining the behaviour of the foreign direct investment inflows in Turkey The main objective of the study is to ascertain the nature of the obstacles and impediments to the greater flow of foreign direct investments into Turkish economy for the recent period by focusing on the results of a questionnaire applied to the executives of 52 multinational corporations operating in Turkey in 2006.
Keywords: Foreign Direct Investment; Turkey; institutions; INTERNATIONAL INVESTMENT; FDI INFLOWS; COUNTRIES; IMPACT; STATES